Cost-effectiveness of telehealth for patients with raised cardiovascular disease risk: evidence from the Healthlines randomised controlled trial - Dixon, Padraig; Hollingshurst, Sandra; Edwards, Louisa; Thomas, Clare; Gaunt, Daisy; Foster, Alexis; Large, Shirley; Montgomery, Alan A.; Salisbury, Chris (BMJ Publishing Group Ltd, 2016)
Objectives: To investigate the cost-effectiveness of a telehealth intervention for primary care patients with raised cardiovascular disease (CVD) risk. Design: A prospective within-trial patient-level economic evaluation conducted alongside a randomised controlled trial. Setting: Patients recruited through primary care, and intervention delivered via telehealth service. Participants: Adults with a 10-year CVD risk ≥20%, as measured by the QRISK2 algorithm, with at least 1 modifiable risk factor. Intervention: A series of up to 13 scripted, theory-led telehealth encounters with healthcare advisors, who supported participants to make behaviour change, use online resources, optimise medication and improve adherence. Participants in the control arm received usual care. Primary and secondary outcome measures: Cost-effectiveness measured by net monetary benefit at the end of 12 months of follow-up, calculated from incremental cost and incremental quality-adjusted life years (QALYs). Productivity impacts, participant out of pocket expenditure and the clinical outcome were presented in a cost-consequences framework. Results: 641 participants were randomised—325 to receive the telehealth intervention in addition to usual care and 316 to receive only usual care. 18% of participants had missing data on either costs, utilities or both. Multiple imputation was used for the base case results. The intervention was associated with incremental mean per-patient National Health Service (NHS) costs of £138 (95% CI 66 to 211) and an incremental QALY gain of 0.012 (95% CI −0.001 to 0.026). The incremental cost-effectiveness ratio was £10 859. Net monetary benefit at a cost-effectiveness threshold of £20 000 per QALY was £116 (95% CI−58 to 291), and the probability that the intervention was cost-effective at this threshold value was 0.77. Similar results were obtained from a complete case analysis. Conclusions: There is evidence to suggest that the Healthlines telehealth intervention was likely to be cost-effective at a threshold of £20 000 per QALY.